The Middle Stone Age human remains from Diepkloof Rock Shelter (Western Cape, South Africa) - (:unkn) unknown (My University, 2013)
In the course of recent excavations at Diepkloof Rock Shelter (South Africa), three human remains were found in the Middle Stone Age layers. These human remains are two pedal phalanges (intermediate and distal) from a fifth ray, which belong to the same individual, and a deciduous first lower molar. The layers in which they were found represent the end of the Howiesons Poort and the beginning of post-Howiesons Poort occupation, and are radiometrically dated to MIS 3, between 45 and 65 kyr ago. They are thus very close in time to the assumed period of anatomically modern humans (AMH) dispersal out of Africa into Eurasia, a period for which very few remains are available in the African fossil record. Here, we describe these new remains and compare their morphology and dimensions to samples of African and Eurasian Pleistocene and Holocene humans. Our results show that the human remains from Diepkloof Rock Shelter fall well within the range of variation of AMH. The phalanges are of very small size and indistinguishable from those of recent humans. In addition, our analysis of the dm1 underlines a large size variation at the end of the MIS 4/beginning of the MIS 3 in the Western Cape. The discovery of human remains at Diepkloof Rock Shelter, albeit limited to three small bones, enriches a poorly represented chronological period of the African hominin fossil record.
Keywords: African Research